Updates on gas hydrate investigation, exploration and production in the world and further direction of its investigation and exploration in Vietnam - Anh Duc Nguyen (Petrovietnam Journal, 2022)
Gas extracted from gas hydrate is an unconventional source of natural gas with high potential, being common both in terrestrial deposits in the Arctic and in marine deposits along continental margins. Vietnam is located in an area that is assessed to have a good potential of gas hydrate. In recent years, the investigation, exploration and trial production of gas hydrate have been paid much attention and strongly deployed in many countries. A series of key projects of geological-technical characterisation, resources assessment, and trial production have been carried out and obtained encouraging results in many regions around the world. In Vietnam, there have been general studies, preliminary assessment of gas hydrate premises and indicators.The article summarises the current status of the investigation, exploration and exploitation of gas hydrate in the world and especially in Japan, China, and makes suggestions on further direction of its investigation and exploration in Vietnam.